2019
DOI: 10.1007/s10029-019-02060-1
|View full text |Cite
|
Sign up to set email alerts
|

Is there a role for prophylactic mesh in abdominal wall closure after emergency laparotomy? A systematic review and meta-analysis

Abstract: Background Incisional hernias are a common complication of emergency laparotomy and are associated with significant morbidity. Recent studies have found a reduction in incisional hernias when mesh is placed prophylactically during abdominal closure in elective laparotomies. This systematic review will assess the safety and efficacy of prophylactic mesh placement in emergency laparotomy. Methods A systematic review was performed according to the PROSPERO registered protocol (CRD42018109283). Papers were dual sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
0
21
1
1
Order By: Relevance
“…In the two previous studies on this topic, the SSI rate in a Swiss study was 60% and, respectively, only 17% in a Spanish study (11,12) .This reflects differences in their patient selection, as there were only subjects with peritonitis in the first study, while all kinds of emergency laparotomies were included in the latter. Neither of the studies included in the only meta-analysis on the topic were randomized controlled trials (2). There were also many methodological differences in both the mesh itself and the mesh placement in these two studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the two previous studies on this topic, the SSI rate in a Swiss study was 60% and, respectively, only 17% in a Spanish study (11,12) .This reflects differences in their patient selection, as there were only subjects with peritonitis in the first study, while all kinds of emergency laparotomies were included in the latter. Neither of the studies included in the only meta-analysis on the topic were randomized controlled trials (2). There were also many methodological differences in both the mesh itself and the mesh placement in these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…There were also many methodological differences in both the mesh itself and the mesh placement in these two studies. Thus, the conclusion of the only systematic review paper published on the topic was that there is a limited amount of data available for assessing the effect and safety of the use of prophylactic mesh in an emergency laparotomy setting (2). Thus, randomized control trials are required to address this important clinical question.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesh reinforcement in emergencies is controversial, and there is a lack of high-quality studies on this issue. On the one hand, a recent meta-analysis concluded that there was inadequate evidence to recommend its use in a standardized approach 17 ; on the other hand, a randomized control trial demonstrated that prophylactic mesh in EMLs reduced the incidence of dehiscence fascia when analyzing short-term outcomes, but with a higher incidence of surgical site infection (SSI) in the mesh group 18 . Surgical site occurrences (SSO) and acute and chronic infection are the main concerns for surgeons when implementing a prophylactic mesh, especially in the emergency setting, apart from other complications such as chronic pain and intestinal stulas 19 .…”
Section: Introductionmentioning
confidence: 99%